Do androids dream of autobiography? - A. D. Blizhenskiy (Омский научный вестник: Серия "Общество. История. Современность")
The modern development of ideas and technologies of artificial intelligence adds practical significance to philosophical debates concerning questions of identity and personal identity. The aim of this article is to demonstrate the advantage of the narrative approach for describing the identity of cybernetic organisms. For this purpose, a mental experiment is formulated to download the consciousness of a scientist into the body of an android. At the end of the article the author discusses a potential hierarchy of narrative criteria.